THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE CIVIL SERVICE POLICE UNIT AND FIRE DEPARTMENT OF SIDENRENG RAPPANG REGENCY - Nur Azizah; Gazali Amin; Auliyah Nurwafiyyah (Jurnal Mahasiswa Manajemen, 2024)
Nur Azizah. 2024. The Effect of Work Discipline on Employee Performance in the Civil Service Police Unit and Fire Department of Sidenreng Rappang Regency. This research aims to investigate the influence of work discipline on the performance of employees of the Civil Service Police Unit and Fire Department of Sidenreng Rappang Regency. Work Discipline is an important factor that supports optimal supervisor performance. The ability of employees to know the rules and carry out tasks with responsibility will have a positive impact on the productivity and effectiveness of the organization. The population of this study was 318 employees. The sample measurement technique uses the Slovin formula with a margin of error of 11%, so the number of samples used is 66 respondents, selected through a random sampling technique. Data was collected through questionnaires. The results of the analysis show that there is a significant influence of work discipline on employee performance, with the calculated t value (3.507) which is greater than the t table (1.998). Therefore, the hypothesis which states that there is an influence of work discipline on employee performance can be accepted. The coefficient of determination (R Square) value is 16.1%, indicating that 16.1% of employee performance variability can be explained by work discipline, while the remaining 83.9% is influenced by other factors outside the variables studied.